A new Miopsalis from Mindanao supports a biogeographic umbilicus between Borneo and the southern Philippines (Arachnida: Opiliones: Cyphophthalmi: Stylocellidae) - Schmidt, Stephanie M.; Clouse, Ronald M.; Sharma, Prashant P. (Zootaxa, 2020)
A new species of Cyphophthalmi belonging to the Southeast Asian genus Miopsalis Thorell, 1890 is described and illustrated using SEM and confocal microscopy. The species is known from two localities in the northern part of Mindanao and constitutes only the second described Cyphophthalmi species endemic to the Philippines. Sequence data obtained from this species show that it is phylogenetically distinct from two juvenile specimens previously collected from Bangaray Kimlawis (southern Mindanao) in 2009. The new Miopsalis is clearly distinguishable from other Miopsalis by characters pertaining to spermatopositor morphology.